HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PENURUNAN RASA NYERI PERSALINAN DI KLINIK RAWAT INAP NU MADINAH PUJON KABUPATEN MALANG: The Relationship Between the Level of Knowledge and Family Support on The Reduction of Labor Pain in The NU Madinah Pujon Inpatient Clinic - Mufida Annisa Rahmawati; Wiqodatul Ummah; Eti Kuswandari; Fitria Aisyah; Novi Budi Ningrum (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Pain during labor is a concrete condition that threatens the birth mother, causing feelings of tension, worry and fear. For this reason, pregnant women try to be successful in dealing with this situation as best as possible until the time of delivery arrives, so support from their husband and family is really needed during the birth process, so that the mother feels safe and comfortable during the birth process. The sampling method was a total sampling of 30 pregnant women who experienced pain during childbirth. The data analysis method used is simple linear regression analysis. Based on the results of research at the NU Madinah Pujon inpatient clinic, there is a calculated T value for the family support variable (X2) of 6.986 > T table 2.048, meaning there is a significant relationship between family support (X2) and a decrease in labor pain (Y). The conclusion in this case is that family support will bring a feeling of joy, a sense of security, a sense of satisfaction and a sense of comfort, which will make the mother in labor feel that she is getting emotional support which will affect her mental well-being, and can relax when the mother feels pain.